Computer Assisted Sperm Analysis (CASA) em software livre empregado em análises espermáticas de peixes: cientometria e aplicação em rotina de reprodução artificial - Neumann, Giovano (2015)
This dissertation is based on the development of two separate scientific papers. (1) First article it is a scientometric analysis: In 2007 was released in the scientific means by Wilson-Leedy and Ingermann, the first article using the CASA free software in sperm mobility analysis for fish, for this study, from of scientometric techniques, the contribution has been assessed and the impact that the article caused the scientific community. It also evaluated the frequency in the number of publications using andrologic analysis in fish, from 2007 to 2014 in four magazines that publish articles related to this topic. Were evaluated under articles made soundness analysis in fish using any existing CASA system, the variables used and ways to interpret the results to determine the sperm viability and correlate the sperm motion parameters with the potential fertilization. For scientometry CASA launching the contribution in free software took place in the google scholar search to get all the work that had quoted the article. For scientometry of items with fish using CASA, was conducted using the search index of ScienceDirect. And to assess the variables and the interpretations made by the authors, harvest characteristics of the materials and methods and results in the articles. It was found 123 quotes Wilson-Leedy article and Ingermann these, 94 are articles, of which 66 were performed with fish, and 35 of these conducted their research using CASA in free software, and there was an increase of 85% in citing publications the author reference. In the search for articles that use in fish soundness analysis, an increase of 59.4% from 2007 to 2014. Of the publications articles using any home system for the assessment of sperm motility in fish, 75.76% of the two work assesses or more times the spermatic movement, 51.52% use at least four of the characteristics generated by CASA, about ¼ of the work validated the CASA results with fertilization and hatching of eggs and used statistical models to group correlated variables CASA and explanations them, less than 10% of articles explores statistical modeling in sperm kinetics and to explain the characteristics generated by CASA on sperm fertility. The article by Wilson-Leedy and Ingermann contributed to the advancement of research with fish sperm, and sperm was used in the evaluation of other animals and other cells also concluded that little is known of the relationship of some sperm variables generated by CASA with fertility sperm in fish. And the researchers do not use in full the resources of the CASA system. (2) According to an article this is an experiment of artificial reproduction: The objective of this study was to evaluate the interactive effects of the relationship or independent mobile sperm: oocyte and sperm speed on artificial reproduction procedures with the use of semen catfish (Rhamdia quelen) cryopreserved. Through the Computer Assisted Sperm Analysis (CASA) were evaluated in six replicates motility and sperm velocity of cryopreserved semen from eight seconds of its activation and to each according to the end of the spermatic movement. For the fertilization test an experimental design was used in a factorial (6x3x3) consists of six mobile sperm relations: oocyte (70,000, 90,000, 110,000, 130,000, 150,000 and 170,000), three sperm speeds (60, 40 and 20μm.s-1) and three experimental replicates or blocks (pools of oocytes from three groups of female). Activation curves of sperm (kinetic) have been prepared with the help of non-linear statistical model. The effects were evaluated on the fertilization, hatching and normal larvae. In evaluating the variables, the response surface analysis showed no interaction effect (p>0.05) between the relationship moving sperm: oocyte and sperm speed, on the fertilization rates, hatching and normal larvae. Only linear effect was found (p<0.05) of sperm speed under the fertilization rates and hatching eggs. According to the results, it is concluded that there is no difference between the use of 70,000 up to 170,000 mobile sperm for each oocyte on the reproductive success in terms of fertilization rate, hatching and larval normality of catfish (Rhamdia quelen) and that the value of the sperm velocity is decisive on the reproductive success of sperm catfish (Rhamdia quelen) decreasing the fertilization and hatching rates as decreases sperm speed.